The chronology and architectural features of Masjid Jamek Sultan Abdul Samad, Kuala Lumpur - Abdul Rahim, Asiah; Sapian, Abdul Razak; Aripin, Srazali; Zubir, Hazwan; Abd Samad, Nur Amirah (Fatih Sultan Mehmet Vakif University, 2024)
This paper is to present the outcome of an analytical study of the part of Masjid Jamek history and chronology, architectural influences, and the site context of the masjid, and how the structure affects the surrounding context, the culture, the society and the economic activities of Kuala Lumpur until this day. Masjid Jamek Sultan Abdul Samad also known as Masjid Jamek Kuala Lumpur is located in Jalan Tun Perak, Kuala Lumpur. The objectives of the studies are: a) Increase the understanding and appreciation of Islamic Architectural Heritage of the Muslim World and outside it, b) Learn the techniques of measured drawings of heritage buildings with an emphasis on the building construction, detailing, research and documentation of the historical aspects of the building and its development, c) Appreciate the total concept and richness of the architectural as well as to be able to value the environment and to understand the socio-economic-cultural way of life of local inhabitants. The methodology applied in this study is using both qualitative and quantitative methods. The data collection for the qualitative method uses interviews, case studies and observation, while the quantitative method uses quantitative observation which involves numerical data and measurements of the building. The data obtained from various methods are documented in reports and measured drawings. In conclusion, this research findings attempt to provide the chronology and history of the masjid for a better understanding of the spreading of Islam in Selangor and the history that led to the establishment of Kuala Lumpur as the national capital of Malaysia.